Cover Picture: Ultra‐Low‐Field NMR Relaxation and Diffusion Measurements Using an Optical Magnetometer (Angew. Chem. Int. Ed. 37/2014). Issue 37 (30th July 2014) - Ganssle, Paul J.; Shin, Hyun D.; Seltzer, Scott J.; Bajaj, Vikram S.; Ledbetter, Micah P.; Budker, Dmitry; Knappe, Svenja; Kitching, John; Pines, Alexander
<x xml:space="preserve">Abstract</x> An optical magnetometer used for making ultra‐low‐field NMR measurements of relaxation and diffusion has the chemical sensitivity required to distinguish between hydrocarbons and water in Earth's magnetic field (0.5 G). P. J. Ganssle, A. Pines et al. describe in their Communication on page 9766 ff., this important proof‐of‐concept for the commercial applicability of these robust, portable NMR sensors, particularly in the context of oil‐well logging.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>